Construction of solutions to a nonlinear critical elliptic system via local Pohozaev identities
In this paper, we investigate the following elliptic system with Sobolev critical growth equation* cases -Δ u+P(|y’|,y’’)u=u^2^*-1+β2u^2^*/2-1